2017
DOI: 10.2174/0929866524666170223142452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Non-Fiber Carbohydrates on Composition and Function of Gut Microbiome in Monogastrics: A Review

Abstract: Non-fiber carbohydrates (NFC) have a crucial function on the gut health of monogastrics. This paper aims to review the relevant published materials on the influence of NFCs on the gut's microbial population and composition in monogastrics, and points out the areas of the required research. Total bacteria count and Lactobacillus sp. were decreased with an increase in composition of dietary NFC intake, as well as accompanied by a decrease in the short-chain fatty acids (SCFAs) levels. Consequently, some metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In this study, all treatments and the control showed less effect on the abundance of Prevotella, Phascolarctobacteroides, Parabacteroides, Ochrobactru, and unclassified Commenadaceae genera. Previously, other studies revealed that Prevotella and Bacteroidetes genera and phylum were abundant in the gut when fibrous diets were used [40]. In this study, only Bacteroidetes were abundant, while marginal levels of Prevotella were observed.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, all treatments and the control showed less effect on the abundance of Prevotella, Phascolarctobacteroides, Parabacteroides, Ochrobactru, and unclassified Commenadaceae genera. Previously, other studies revealed that Prevotella and Bacteroidetes genera and phylum were abundant in the gut when fibrous diets were used [40]. In this study, only Bacteroidetes were abundant, while marginal levels of Prevotella were observed.…”
Section: Discussionsupporting
confidence: 52%
“…Fiber intake modulates gastrointestinal physiology and normalizes bowel movement [ 25 ]. Dietary fiber is the portion of consumed food that is composed of carbohydrates that are resistant to digestion and absorption in the small intestine and fermented partially or completely in the large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal epithelial cells in pigs are the most similar models to the human gastrointestinal epithelial cells [ 43 ]. Thus, using of SBA in high levels for human nutrition could exhibit relevant level of gastrointestinal cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%